Effects of artificial rearing and restricted nutrient intake during the first three weeks of life on later performance and carcass characteristics of pigs - G L Allee; M Noll (Kansas Agricultural Experiment Station Research Reports, 1980)
Sixty pigs from nine 1itters were allotted, 24 hours after birth, by litter, sex, and birth weight to three treatments: A) sow reared, B) artificially reared and fed milk replacer ad libitum twice daily (artificially reared-unrestricted), and C) artificially reared and restricted to 50% of the nutrient intake of treatment B (artificially reared-restricted). Artificially reared pigs were housed in individual cages during the 20 day treatment period. After 21 days of age, pigs were fed corn-soybean meal diets ad libitum to slaughter at 220 pounds. Average daily gains and pig weights at 21 days differed significantly (P<.0l) different among all treatments.; Swine Day, Manhattan, KS, November 13, 1980
Keywords: Swine day; 1980; Kansas Agricultural Experiment Station contribution; no. 81-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 388; Swine; Artificial rearing; Performance; Carcass characteristics